Histomorfologia da glande peniana e do báculo de morcegos molossideos e vespertilionideos: uma abordagem comparativa (Chiroptera, Mammalia) - Comelis, Manuela Tosi [UNESP] (2015)
The glans penis morphology of eleven molossid and one vespertilionid species of bats were analyzed histomorphologycaly after diaphanization procedures, histological sections and hematoxylin- eosin and Tushmann's blue staning. In general the penis of the analyzed species has three erectile tissues, with two main, the cavernous tissue and diffuse cavernous tissue and other one with lesser developement, the spongy tissue of the urethra. The two first are well developed, making the most part of penile mass. Differences in the number and localization of these tissues were observed in species of genera. Except for E. furinalis and species of Eumops, the others showed spiniform epidermal projections in the outer covering of the penis, which vary little in morphology, differing in size and distribution over the glans. The baculum is present inside the glans on the species of the genus Molossus, Nyctinomops and Eumops where varied significantly in morphology and size, and were absent in species of the genera Cynomops, Molossops and Neoplatimops. The variability observed in the baculum shows its importance as a taxonomic character, and indicates that the morphological similarities are observed in congeneric species. The results demonstrated a great potential exhibited by the glans penis and baculum as taxonomic characters, mainly to the family and genus level, but also important for species distinction. In conclusion, the present study generated new information about the macro and micro anatomy of the glans penis in Chiroptera, which may be useful in future comparative and taxonomic studies on reproductive aspects of the group that have not been evaluated yet